Solitary Fibrous Tumor of the Central Nervous System: A Report of Two Cases with Emphasis on Diagnostic Pitfalls - Absalom Mwazha; Nondabula Moyeni; Zuzile Zikalala; Gamalenkosi Bonginkosi Nhlonzi (Case Reports in Pathology)
Solitary fibrous tumor (SFT) is a rare primary central nervous system neoplasm that usually presents as a dural-based mass. Awareness of the entity is limited by the rarity of the tumor which renders it prone to misdiagnosis. We present two cases of SFT located in the right parafalx and intraventricular region. The cases were classified as WHO grade 1 and grade 2, respectively. The present study discusses the radiological, histomorphological, and immunohistochemical features of SFT, with emphasis on potential diagnostic pitfalls that may lead to erroneous diagnosis.